Beyond Gender: Interoceptive Sensibility as a Key Predictor of Body Image Disturbances - Akansha M. Naraindas; Marina Moreno; Sarah M. Cooney (Behavioral Sciences, 2023)
Body image disturbance (BID) involves negative attitudes towards shape and weight and is associated with lower levels of interoceptive sensibility (IS) (the subjective perceptions of internal bodily states). This association is considered a risk factor for developing eating disorders (EDs) and is linked to altered sensorimotor representations of the body (i.e., body schema). BIDs manifest across genders and are currently understudied in men. This study investigated gender-related differences in BID and its relationship to the body schema and IS. Data were collected from 86 men and 86 women. BID was assessed using questionnaires measuring self-objectification, state, and trait body dissatisfaction. IS was measured via the MAIA-2. The body schema was indexed via an embodied mental rotation task. Results showed that women reported higher BID than men across all scales. Gender differences in sub-components of interoceptive sensibility were found. Overall, both gender and interoceptive sensibility predicted BID. However, interoceptive sensibility exhibited its own unique association with BID beyond the influence of gender. BID, IS and gender were not significant predictors of performance in the body schema task. Therefore, while gender predicts differences in BID and interoceptive sensibility, there was no evidence of gender-related differences in body schema.